Anomalous transmission of polypyrrole film on gold nanoparticle-immobilized electrode - Hasegawa, Miho; Koshiji, Fukuro; Uchida, Takayuki; Yamada, Katsumi (Japanese Journal of Applied Physics, 2023)
Gold nanoparticles with a uniform particle size were easily immobilized on the transparent electrode by an electrochemical deposition. The polypyrrole film on the obtained nano-structured electrode exhibited anomalous permeation, indicating that this electrode functions as a metasurface.